Odpowiedzi

  • yzik
  • Rozwiązujący
2010-01-31T21:31:30+01:00
(4x)^2 + (3x + 1)^2 = (3 - 5x)^2
16x^2 + 9x^2 + 6x + 1 = 9 - 30x + 25x^2
36x = 8
x = 8/36
x = 2/9
1 5 1
Najlepsza Odpowiedź!
2010-01-31T21:41:07+01:00
1.
(4x)² + (3x + 1)² = (3-5x)²
16x² + 9x² + 6x + 1 = 9 - 30x + 25x²
36x = 8
x = 4,5

a= 4x = 18
b = 3x + 1 = 14,5
c = 3 - 22,5 = |-19,5| = 19,5

2. (3 -2x)² + (3-x)² = (√5x)²
9 - 12x + 4x² + 9 - 6x + x² = 5x²
-18x = -18
x= 1
a = 3 - 2x = 1
b = 3-x = 2
c = √5

3.(√3x)² + (x+1)² = (2-2x)²
3x² + x² + 2x + 1 = 4 - 8x + 4x²
10x =3
x=3/10
a=√9/10 = 3√10/10
b=x + 1 = 13/10
c = 2 - 2x = 14/10

pzdr ;)